Review of Terms and Definitions Used in Descriptions of Running Shoes. - Marchena-Rodríguez, Ana José; Ortega-Ávila, Ana Belén; Cervera-Garvi, Pablo; Cabello-Manrique, David; Gijón-Noguerón, Gabriel (MDPI, 2020)
Objective: Our study aim is to identify and describe the definitions used for different types of running shoes. In addition, we highlight the existence of gaps in these concepts and propose possible new approaches. Methods: This review was undertaken in line with the guidelines proposed by Green et al., based on a literature search (until December 2019) of the PubMed, Web of Science, Scopus, SPORTDiscus and Google Scholar databases. A total of 23 papers met the inclusion criteria applied to identify the definition of running shoes. Results: Although there is a certain consensus on the characteristics of minimalist footwear, it is also described by other terms, such as barefoot-style or barefoot-simulating. Diverse terms are also used to describe other types of footwear, and in these cases, there is little or no consensus regarding their characteristics. Conclusions: The terms barefoot-simulated footwear, barefoot-style footwear, lightweight shoes and full minimalist shoes are all used to describe minimalist footwear. The expressions partial minimalist, uncushioned minimalist and transition shoes are used to describe footwear with non-consensual characteristics. Finally, labels such as shod shoes, standard cushioned running shoes, modern shoes, neutral protective running shoes, conventional, standardised, stability style or motion control shoes span a large group of footwear styles presenting different properties.
Keywords: Calzado deportivo; Footwear; Sports shoes; Running shoes; Conventional running shoes; Minimalist running shoes; Barefoot running; Motion-control shoes